The Pope's exorcist - Avery, Julius; Crowe, Russell, 1964-; Zovatto, Daniel, 1991-; Essoe, Alex; Amorth, Gabriele (Sony Pictures Home Entertainment, 2023)
The Vatican's leading exorcist investigates the possession of a child and unveils a secret conspiracy.
The Chief Exorcist of the Vatican, Father Amorth investigates a young boy's terrifying possession and ends up uncovering a centuries-old conspiracy the Vatican has desperately tried to keep hidden.
Based on the books "An exorcist tells his story" and "An exorcist : more stories" by Father Gabriele Amorth.
Wide screen 1.85:1.
Russell Crowe, Daniel Zovatto, Alex Essoe, Franco Nero, Peter DeSouza-Feighoney.
MPAA rating: R.
Keywords: Amorth, Gabriele -- Film adaptations; Exorcism -- Drama; Demoniac possession -- Drama; Conspiracies -- Drama; Vatican City -- Drama; Horror films; Thrillers (Motion pictures); Film adaptations; Feature films; Fiction films